Regioselective & diastereoselective Synthesis and antibacterial studies of (1’R,2’S)-7’’-chloro-6’’-(2-chloroethyl)-2’-aryl-5’,6’,7’,7a’-tetrahydro-2’H-dispiro[indene-2,3’-pyrrolizine-1’,3’’-indoline]-1,2’’,3-trione through 1,3-dipolar cycloaddition - P.S. HARIKRISHNAN (The Bioscan, 2023)
Regioselective & diastereoselective Synthesis and antibacterial studies of (1'R,2'S)-7''-chloro-6''-(2-chloroethyl)-2'-aryl-5',6',7',7a'-tetrahydro-2'H-dispiro[indene-2,3'-pyrrolizine-1',3''-indoline]-1,2'',3-trione was successfully performed through the 1,3-dipolar cycloaddition of azomethine ylide generated insitu by the reaction between L-proline and ninhydrin with the (3-Z)-6-chloro-3-(benzylidene-5-(2-chloroethyl-1,3-dihydro-2H-indol-2-one. These dispiro compounds were prepared in high yield in shorter reaction time. Since there was no waste produced in the reaction, one can consider this as a green method of synthesis. The synthesised compounds were subjected to the anti-bacterial studies.